A study of the Ghana National Association of Teachers' programmes and its implications for membership commitment - Boh, Johnson Kwaku (My University, 2016)
This study seeks to understand the implications of the Ghana National Association of Teachers’ (GNAT) programmes on members, and to investigate the perception of members regarding their commitment to the union. The period, 1995 to 2014 was chosen because it marked the era of fragmentation of GNAT, and the formation of other teacher-unions which broke the monopoly of GNAT as the sole teachers’ union in Ghana. The main objective of the study is to examine the implications of member commitment on GNAT programmes. Specifically, the study intends to investigate the perceptions of satisfaction, participation and loyalty of union members. It also attempts to examine the responses of the union to challenges within the organization. The study was based on interviews of key informants and a survey of members and former members of GNAT. Structured questionnaires were used as instruments. Data Analysis was by the application of Excel and SPSS (Statistical Package for Social Sciences). Presentations are displayed by graphs, frequency tables and pictorials. In order to understand commitment of respondents, the survey measures members’ satisfaction, participation and loyalty to GNAT. These variables are related to programmes, hence questions on variables were asked in relation to programmes. This study has found out that GNAT membership decline can be partially explained by decline in levels of member participation and satisfaction with programmes. The study, has however noted that despite members’ dissatisfaction with GNAT programmes, the majority of them are still committed to the union. One possible reason for the high loyalty of members could be the value that they attach to the union. The study therefore concludes that the members' perception is not, by itself, a sufficient variable for understanding the union’s decline. The study recommends that the communication system of GNAT be improved. It also recommends that due to changing composition of membership with respect to age and qualifications, there is need to broaden the professional development of members especially those in leadership positions by fashioning programmes to meet their needs. There is also need to engage members in establishing the training needs in the Ghana National Association of Teachers that would be included in the training programmes in order to make them more attractive.
Keywords: Teachers Unions; Ghana